2015
DOI: 10.1016/j.crvi.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the bacterial wilt pathogen Ralstonia solanacearum using a RAPD marker

Abstract: Bacterial wilt caused by Ralstonia solanacearum is a destructive disease of many economically important crop species. A significant variation in wilt incidence and severity in eggplant and potato was observed among the growing areas surveyed. R. solanacearum isolates obtained both from eggplant and potato belong to biovar III, while isolates from eggplant belong to race 1 and isolates obtained from potato belong to race 3. Random amplified polymorphic DNA (RAPD) technique was used as a tool for assessing genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…shows the difference between avirulent colonies that look dark red from the fluidal virulent that are white with pink center [25,29]. In the present study, the colonies were fluidal whitish with a pink center, indicating virulent species of R. solanacearum.…”
Section: Morphological Profiling Of Ralstonia Solanacearummentioning
confidence: 54%
“…shows the difference between avirulent colonies that look dark red from the fluidal virulent that are white with pink center [25,29]. In the present study, the colonies were fluidal whitish with a pink center, indicating virulent species of R. solanacearum.…”
Section: Morphological Profiling Of Ralstonia Solanacearummentioning
confidence: 54%
“…Only Philippines have all of biovars 1-4 and here as elsewhere in Asia, biovar 3 predominates in the lowland regions (Hayward, 1991;CABI, 2017a). However, report from Ahmed et al (2013) and Nishat et al (2015) showed that the R. solanacearum isolates causing bacterial wilt of potato in Bangladesh were belonging to Biovar III and Race 3.…”
Section: Distributionmentioning
confidence: 99%
“…Nishat et al (2015) reported the variation in R. solanacearum isolates of potato which was observed among different growing areas of Bangladesh. It was showed that the isolates were belonged to race 3 biovar III.…”
Section: Races and Biovarsmentioning
confidence: 99%
“…Race 3 affects potatoes and tomatoes but is weakly virulent in other solanaceous crops. Finally, race 4 affects ginger plants in the Philippines, and race 5 affects mulberry plants in China [3].…”
Section: Introductionmentioning
confidence: 99%
“…solanacearum is a gram-negative soil inhabitant that is motile due to the presence of one to four polar flagella. Additionally, is aerobic and can survive in temperatures ranging from 10°C to 41°C and can be found in tropical, subtropical and temperate zones [3]. This pathogen is known for causing bacterial wilt in economically important crops worldwide and can parasitize approximately 250 species belonging to 54 plant families [4,5].…”
Section: Introductionmentioning
confidence: 99%